Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1007/bf02986617
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of CD7+CD56+ Phenotype and Chromosome 5 Abnormalities for Acute Myeloid Leukemia M0

Abstract: Myeloid/natural killer (NK) cell precursor acute leukemia is an entity of acute leukemia characterized by poor prognosis and a CD7+CD56+ myeloid antigen+ phenotype without light-microscopic myeloperoxidase reactivity. This disease shares several clinical characteristics with acute myeloid leukemia (AML) M0. To clarify the relationship between these 2 leukemias, we analyzed 105 cases of AML M0. Among them, 17 were CD7+ and CD56+, 77 were negative for either antigen, and 11 could not be determined. CD7+CD56+ AML… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…11 The expression of CD56 has been shown to be of prognostic relevance in certain hematologic malignancies. [5][6][7]29 In the small series of Montero et al, an inferior survival of CD56 + T-ALL was reported. 8 Therefore, we analyzed the impact of CD56 expression on outcome in our series.…”
Section: Discussionmentioning
confidence: 99%
“…11 The expression of CD56 has been shown to be of prognostic relevance in certain hematologic malignancies. [5][6][7]29 In the small series of Montero et al, an inferior survival of CD56 + T-ALL was reported. 8 Therefore, we analyzed the impact of CD56 expression on outcome in our series.…”
Section: Discussionmentioning
confidence: 99%
“…Myeloid antigen-positive T/NK bi-potential progenitors are believed to develop by transformation into myeloid/NK cell precursor acute leukaemia [15,16]. NK-cell lineage committed progenitors are also hypothesized to transform to blastic NK-cell lymphoma (BNKL) or precursor NKcell acute lymphoblastic leukaemia/lymphoma (NK-ALL) [17,18].…”
Section: Pathological Transformation Of Nk-cellsmentioning
confidence: 99%
“…These cases were classified as AML M0 according to the FAB classification 129,130 , and were distinct from CD56-positive tumors of myeloid/NK cell acute leukemia with mature promyelocytoid morphology 131 , as well as BNKL 99 . However, this form of leukemia was later found to exhibit different clinical characteristics from CD7 − or CD56 − AML M0 132 , and was thus a distinct disease entity among AML subclasses.…”
mentioning
confidence: 99%